2011
DOI: 10.1002/adfm.201100113
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Two‐Layered Chiral Nanoparticles Consisting of Optically Active Helical Polymer/Silica: Preparation and Application for Enantioselective Crystallization

Abstract: This article reports for the first time a novel category of hollow organic@inorganic hybrid two‐layered nanoparticles (NPs), in which the inner layer is formed by optically active helical polyacetylene, and the outer layer by silica. Such NPs show remarkable optical activity and are successfully used for enantioselective crystallization. To prepare such NPs, n‐butyl acrylate undergoes radical polymerization to first form poly(n‐butyl acrylate) (PBA) cores two shells by catalytic polymerization of substituted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
160
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(175 citation statements)
references
References 52 publications
13
160
2
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29] Polymer particles based on chirally helical substituted polyacetylenes also have been prepared and performed interesting optical activity. Such optically active polymer particles were majorly reported by Deng group [43][44][45][46] and are also included in this review article.…”
Section: Introductionmentioning
confidence: 93%
“…[19][20][21][22][23][24][25][26][27][28][29] Polymer particles based on chirally helical substituted polyacetylenes also have been prepared and performed interesting optical activity. Such optically active polymer particles were majorly reported by Deng group [43][44][45][46] and are also included in this review article.…”
Section: Introductionmentioning
confidence: 93%
“…[2][3][4][5] However, we found that two polymers derived from a pair of enantiomeric monomers (as structurally shown in Scheme 1 ) showed the opposite phenomenon. In more detail, the two polymers also adopted helical conformations when existing in the form of nanoparticles.…”
Section: Introductionmentioning
confidence: 93%
“…The polymer solution was prepared following in Scheme 1 ). According to the methodology created by us, [ 2 , 3 ] M 1 and M 2 underwent emulsion polymerization in aqueous media, with Triton X-100 as surfactant and (nbd) Rh + B − (C 6 H 5 ) 4 as catalyst. The detailed preparing processes and experimental conditions were introduced earlier.…”
Section: Synthesis Of Polymer Emulsionmentioning
confidence: 99%
“…[31] Following the same concept, that is, the seed emulsion polymerization strategy presented in Figure 1, we prepared hollow core/shell NPs through a three-step, onepot process, as illustrated in Figure 2. The three steps include the successive emulsion polymerization of BA (step one), emulsion polymerization of SA (step two), and then the solgel process of TEOS (step three) in the same polymerization system.…”
Section: Optically Active Hybrid Materials Constructed From Hspa/silicamentioning
confidence: 99%